The Use of System Dynamics to evaluate print outsourcing scenarios in a public educational institution - Negrini, Fernando (2019)
Information and Communication Technologies (ICT) emerge as a strategic tool, indispensable for the survival of any organization. However, excessive use of ICT can lead to drawbacks such as equipment dependency, rapid obsolescence, and rising maintenance costs. Inefficient use of ICT can result in higher costs for organizations, which may cause them to lose important competitive advantages. In this context, outsourcing printing may be an alternative for institutions to reduce their costs and become more competitive. The aim of this paper is to evaluate scenarios about the financial viability of printing outsourcing in a Federal Higher Education Institution (Instituição Federal de Ensino Superior - IFES). To this end, an exploratory research was conducted, with a quantitative approach, using computational modeling, and using the System Dynamics methodology, with simulation and evaluation of three different scenarios: current scenario, likely scenario, unlikely scenario. The results obtained indicate that the unlikely scenario (100% of leased printers) resulted in lower printing costs over the period of the experiment, totaling R$ 637,828.00; the probable scenario (50% of leased printers) totaled R$ 1,000,480.00; while the current scenario (20% of leased printers) resulted in costs of R$ 1,603,060. With the simulations, it was found that printer leasing (outsourcing printing) is the best financial alternative for IFES, which served as a reference for the study, resulting in lower printing costs compared to printer acquisition. The use of systems modeling to evaluate scenarios has been used to support managers in the decision making involving ICT; however, there were no studies in the literature focused on the financial viability simulation of printer outsourcing. Thus, this work sought to bridge this gap by developing and validating a simulation model that can be applied in different scenarios and types of organizations, and work as a reference for future studies.